The Effect of Problem-Based Learning Method on Learning Outcomes of Pancasila Education For Grade V Students of SDN Baru 06 - Naufal Qoyyum; Ade Hikmat (Green Publisher Indonesia, 2024)
This research aims to improve learning outcomes and determine whether or not there is an influence on Pancasila Education learning outcomes using the Problem Based Learning learning method for students at V SDN Baru 06 for the 2023-2024 academic year. The research method used is a quantitative research method with the research design used being Quasi Experiment with Posttest-only Control Group Design type and the sampling technique used is Purposive Sampling. Next, the data was analyzed for the requirements test, namely the Normality test using the Liliefors test, obtaining the control class Lo < Lt, namely 0.1478 < 0.1674 and the experimental class Lo < Lt, namely 0.1353 < 0.1645, so it can be concluded that both data are normally distributed. While the homogeneity test using Fisher's test obtained Fcount < Ftable, namely 1.342 < 1.898, so it can be concluded that the homogeneity test has homogeneous distribution of group variance data. In hypothesis testing, the t-test was used to obtain tcount > ttable, namely 3.303 > 2.004. Thus, Ho is rejected and H1 is accepted, which states that there is an influence of the problem based learning method on the Pancasila education learning outcomes of class V students at SDN Baru 06. With the effect size test results of 0.817, which means the influence of the problem based learning learning method is very high on the results. Learning Pancasila Education for Class V Students of SDN Baru 06.